The influence of microangiopathy in Diabetics with antiplatelet drugs - Bremer, G; Richter, O; Jacobi, E; Koschinsky, T (Thrombosis and Haemostasis, 1981)
It is well kown that microangiopathy is associated with shortened platelet survival. Therefore a pilot study was performed to test several antiplatelet drugs with respect to their ability to increase platelet survival. The study was confined to 18 patients with long standing Diabetes mellitus and microangiopathv of I.- II. degree, exhibiting platelet survival times less than 7 days. The patients were treated with antiplatelet drugs. Dipyridamole with several combination of Acetylsali- cylicacid (ASA) and Sulfinpyrazon.1. 225 mg Dipyridamole and 990 mg ASA per day, 2. 225 mg Dipyridamole and 300 mg ASA per day, 3. 150 mg Dipyridamole and 150 mg Sulfinpyrazon per day.Platelet survival was determined by the method described by Harker. The resultant survival curves were analysed by a computer program written by Murphy and Francis which is based on the multine hit model for platelet survival.The results of the study are: After 10 days treatment the platelet survival was markedly increased under each of the combination.If one assumes that there exists a causal relationship between microangiopathy and platelet survival,a long-term treatment by antiplatelet drugs may be a prophylaxis against microangiopathy in diabetics.